NuGingaJS: a Full Portable ITU-T H.761 Ginga Middleware for DTV and IPTV - Braga, Rodrigo; Klehm, Volnei; Gama, Lauro; Mello, Michael; Paiva, Taynara; Nogueira, Dina; Beltrão, Ruddá; Lima, Addison; Santana, Leonardo; Nascimento, Lois; Lee, Chak; Travassos, Felipe (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
Legacy analog transmission technologies have already been replaced by the modern digital television (DTV) broadcasting in several countries. Besides having better audio and video quality, the modern DTV provides interactive experience via applications that are encoded in signals transmitted by broadcasters. There are some implementations available on the market that handle DTV interactivity. However, most of these solutions require large efforts to be converted to new upcoming platforms. The aim of this article is to provide a detailed description of a web-based implementation of Ginga-NCL standard for interactivity adopted in Latin America countries, such as Brazil and Argentina. This implementation uses modern technologies, like Emscripten and WebAssembly, towards a solution that works on any platform with an embedded web browser.